2023
DOI: 10.1002/ptr.8049
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanism of Paeonol on central nervous system

Rui Wu,
Yanfang Liu,
Fang Zhang
et al.

Abstract: Cerebrovascular diseases involve neuronal damage, resulting in degenerative neuropathy and posing a serious threat to human health. The discovery of effective drug components from natural plants and the study of their mechanism are a research idea different from chemical synthetic medicines. Paeonol is the main active component of traditional Chinese medicine Paeonia lactiflora Pall. It widely exists in many medicinal plants and has pharmacological effects such as anti‐atherosclerosis, antiplatelet aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 195 publications
0
1
0
Order By: Relevance
“…Paeonol (2′-hydroxy-4′-methoxyacetophenone), a bioactive ingredient in the Cortex Moutan of traditional Chinese medicine, has been found to inhibit antiplatelet aggregation and anti-inflammatory activity and suppress oxidative stress ( Zhang et al, 2019 ). Numerous studies have demonstrated that paeonol can protect the brain from damage and reduce the area of cerebral infarction caused by ischemic stroke ( Zhao et al, 2018 ; Wu et al, 2023 ). Nevertheless, paeonol has poor water solubility and a high metabolic rate, both of which impede its use in clinical applications ( Zhang M. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paeonol (2′-hydroxy-4′-methoxyacetophenone), a bioactive ingredient in the Cortex Moutan of traditional Chinese medicine, has been found to inhibit antiplatelet aggregation and anti-inflammatory activity and suppress oxidative stress ( Zhang et al, 2019 ). Numerous studies have demonstrated that paeonol can protect the brain from damage and reduce the area of cerebral infarction caused by ischemic stroke ( Zhao et al, 2018 ; Wu et al, 2023 ). Nevertheless, paeonol has poor water solubility and a high metabolic rate, both of which impede its use in clinical applications ( Zhang M. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%